New forms of employment in a globalised world: three figures of knowledge workers. (1st December 2016) - ,; ,
Abstract : This article analyses three figures of knowledge workers – performing arts workers, salaried entrepreneurs and makers – examined through their institutional regulation and, mainly, their practices of appropriation of knowledge. All of these workers are positioned outside the regular rules of employment, but their activity is framed by different institutional architectures. Performing art workers are formally salaried but concretely they are almost independent, salaried entrepreneurs are quasi-entrepreneurs even when they are formally salaried, while makers produce autonomous spaces out of employment relationships. These figures are not analysed as professional groups, but through their practices of appropriation of knowledge. This analysis leads to the conclusion that, contrary to the neoliberal model of 'self-entrepreneurship', these experiences open up the possibility of producing a new form of autonomy gained by collective action, far from the idealised concept of individualistic autonomy.